Effect of metal complexation on the equilibrium between methylphosphepine and methylphosphanorcaradiene and their benzo analogues. (26th July 2016) - Chen, Xiaohong; Yuan, Li; Leng, Xueqin; Jin, Rong; Du, Quan; Feng, Hao; Xie, Yaoming; Bruce King, R.; Schaefer, Henry F.
Abstract : Methylphosphepine and its norcaradiene isomer as well as their benzo-derivatives are predicted to form energetically closely spaced η 4 -tetrahapto and η 3 -trihapto complexes with the transition metal units. Abstract : Theoretical studies are reported on methylphosphepine, methylbenzophosphepine, their norcaradiene isomers, and their metal complexes with Fe(CO)3 and CpCo (Cp = η 5 -C5 H5 ) units. Both methylphosphepine and methylphosphanorcaradiene are C6 H6 PCH3 species existing as anti / syn stereoisomer pairs with the methylphosphepine structures at slightly higher energies. The transition states for the interconversion of these isomers and their benzo derivatives lie ∼20 kcal mol −1 in energy above the methylphosphanorcaradiene isomers. Complexation of either C6 H6 PCH3 ligand with the transition metal units Fe(CO)3 and CoCp leads to energetically closely spaced η 4 -tetrahapto and η 3 -trihapto isomers of the methylphosphepine complexes and η 4 -tetrahapto isomers of the methylphosphanorcaradiene complexes. However, the bis(dihapto) (η 2, 2 -C6 H6 PCH3 )Fe(CO)3 and (η 2, 2 -C6 H6 PCH3 )CoCp complexes involving coordination of non-adjacent CC double bonds lie at significantly higher energies. Fusion of a benzene ring to the C6 H6 PCH3 rings in methylphosphepine and methylphosphanorcaradiene leads to significantly different structures of their lowest energy metal complexes. Thus the lowest energy (C10 H8 PCH3 )Fe(CO)3 and (C10 H8 PCH3 )CoCp structures are η 2, 2 and η 4 methylbenzophosphepine complexes, which avoid using any carbon atoms of the benzene ring in the ligand for metal complexation. Higher energy (C10 H8 PCH3 )Fe(CO)3 and (C10 H8 PCH3 )CoCp structures have tetrahapto ligands with one or both CC double bonds of the benzene ring complexed with the metal atom.